Sodium ion battery and preparation method thereof

By optimizing the positive and negative electrode components of sodium ion battery and electrolyte components, the performance limitations of sodium ion battery in high-speed usage scenarios are solved, and the high performance of 8C continuous charging, 10C continuous discharge and 50C pulse discharge is achieved, which is suitable for applications in a variety of harsh conditions.

CN119650818AInactive Publication Date: 2025-03-18安徽青钠能源科技有限公司 +2

Patent Information

Application Number
CN202411625224.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

At this stage, sodium ion batteries have a problem that the maximum discharge rate is almost difficult to exceed 4C in high-speed usage scenarios, which limits their use in high-speed applications.

Method used

By optimizing the components of the positive and negative electrode sheet, sodium nickel ferromanganate, conductive agent SP, CNT and binder PVDF are used as the positive electrode sheet, hard carbon, conductive agent SP, CNT, CMC and binder SBR are used as the negative electrode sheet, and high pore coating separators and sodium salt organic solvent system electrolyte are used to improve the charging and discharge performance of the battery.

Benefits of technology

The ultra-high rate performance of 8C continuous charging, 10C continuous discharge and 50C pulse discharge is achieved. At the same time, 30C pulse discharge can still be achieved at -20℃, meeting the application needs of high temperature and high humidity, high frequency vibration and wide temperature harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the field of batteries, in particular to a sodium ion battery and a preparation method thereof. The sodium ion battery comprises a positive plate, a negative plate, electrolyte and a diaphragm, the positive plate comprises nickel iron sodium manganate, a conductive agent SP, CNT and a binder PVDF; the negative plate comprises hard carbon, a conductive agent SP, CNT, CMC and a binder SBR; and the mass ratio of the sodium ferro-nickel manganate to the conductive agent SP to the CNT to the binder PVDF in the positive plate is (95.5 to 96.5) to (1.2 to 1.9) to (0.4 to 1.2) to (1.2 to 1.6). The invention provides an ultrahigh-rate sodium-ion battery with excellent charge-discharge performance, and the sodium-ion battery can realize 8C continuous charge, 10C continuous discharge and 50C pulse discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a sodium ion battery and a preparation method thereof. Background Art

[0002] High-rate batteries are batteries with high charge and discharge rate capabilities. These batteries can quickly release electrical energy to provide high power output and are suitable for occasions that require instantaneous high energy, such as electric vehicles, electric ships, power tools, drones, start-stop power supplies, etc. For automotive start-stop power supplies, lead-acid batteries are currently widely used. However, lead-acid batteries are not the best choice for future starting batteries. They have many shortcomings such as long charging time, short life, low energy density, and large self-discharge. The issuance of the "lead ban" also announced the end of its prospects. Therefore, the field of starting batteries needs to find a solution with better comprehensive performance, and sodium ions have lower solvation energy and smaller Stokes radius, so sodium ions have better interfacial reaction kinetics, and sodium ion batteries are more suitable for high-rate charge and discharge scenarios.

[0003] Due to the large discharge polarization, low discharge capacity and high discharge temperature rise during high current discharge, the maximum discharge rate of sodium-ion batteries, especially those with large cylindrical structures, is almost impossible to exceed 4C at this stage, thus limiting the application of sodium-ion batteries in high-rate usage scenarios. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a sodium ion battery and a preparation method thereof. The present invention provides an ultra-high rate sodium ion battery capable of achieving 8C continuous charging, 10C continuous discharging, and 50C pulse discharging.

[0005] In the first aspect, the sodium ion battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator; the positive electrode sheet comprises sodium nickel iron manganese oxide, a conductive agent SP, CNT and a binder PVDF; the negative electrode sheet comprises hard carbon, a conductive agent SP, CNT, CMC and a binder SBR; the mass ratio of the sodium nickel iron manganese oxide, the conductive agent SP, CNT and the binder PVDF in the positive electrode sheet is (95.5-96.5): (1.2-1.9): (0.4-1.2): (1.2-1.6). The sodium ion battery provided by the present invention optimizes the components of the positive and negative electrode sheets to obtain an ultra-high rate sodium ion battery with excellent charge and discharge performance.

[0006] Preferably, the foil material of the positive electrode sheet and / or the negative electrode sheet comprises a substrate and a carbon coating layer covering the surface of the substrate, the substrate thickness is 12-25 μm, and the carbon coating layer thickness is 1-3 μm; the foil material is preferably a carbon-coated aluminum foil. In the present invention, the use of the above-mentioned carbon-coated foil material for the positive and negative electrode sheets can further reduce the electrode sheet impedance, which is beneficial to improving the overall performance of the battery.

[0007] In the present invention, the coating surface density of the positive electrode sheet is 140-260g / m², preferably 220-260g / m², and the compaction density is 3.0-3.3g / cm³. The coating surface density of the negative electrode sheet is 90-120g / m², and the compaction density is 0.9-1.1g / cm³.

[0008] More preferably, in the positive electrode sheet, the mass ratio of the sodium nickel iron manganese oxide, the conductive agent SP, the CNT and the binder PVDF is (95.9-96.2): ​​(1.5-1.8): (0.5-0.8): (1.3-1.5).

[0009] More preferably, in the negative electrode sheet, the mass ratio of the hard carbon, the conductive agent SP, CNT, CMC and the binder SBR is (94-95): (1-1.5): (0.5-1): (1.2-1.8): (2.3-2.8).

[0010] Preferably, the CNT is a multi-walled carbon nanotube MWCNT and / or a single-walled carbon nanotube SWCNT.

[0011] Preferably, the particle size of the sodium nickel iron manganese oxide in the positive electrode sheet and / or the hard carbon in the negative electrode sheet is 2-8 μm. In the present invention, by optimizing the positive and negative electrode main materials and selecting 2-8 μm small particle size main materials, and at the same time, the positive and negative electrodes are both connected through the conductive agent SP and CNT to build a conductive network, which can further reduce the impedance and improve the migration rate of ions.

[0012] Preferably, the diaphragm is a ceramic diaphragm, preferably a ceramic diaphragm coated with aluminum oxide, a ceramic diaphragm coated with boehmite or a PE ceramic diaphragm, and the porosity of the diaphragm is 40-50%, such as 45%, 46%, 48%, 49%, etc. and any value therebetween. In the present invention, the use of a high-porosity coated diaphragm, especially the above-mentioned preferred diaphragm, can further increase the diaphragm liquid retention capacity and improve the ion penetration rate.

[0013] Preferably, the electrolyte is a sodium salt organic solvent system. The present invention does not limit the specific composition of the electrolyte. For example, the sodium salt may include but is not limited to sodium hexafluorophosphate, etc., and the organic solvent may include but is not limited to ethyl methyl carbonate in the present invention, etc. In the present invention, the use of the sodium salt organic solvent system has high conductivity, and the sodium salt organic solvent system has low viscosity, which helps to improve the ion migration rate.

[0014] Preferably, the sodium ion battery is a large cylindrical sodium ion battery, and the positive terminal and the negative terminal adopt a full-pole lug structure. In the present invention, both the positive and negative terminals of the winding core adopt a full-pole lug structure to increase the electron transfer channel and take into account rapid heat dissipation.

[0015] In the present invention, the large cylindrical sodium ion battery comprises a steel shell, a combined cap, a winding core, positive and negative electrode current collecting plates, and an electrolyte, and the winding core comprises a positive electrode sheet, a negative electrode sheet, and a diaphragm.

[0016] In a second aspect, the present invention provides a method for preparing the sodium ion battery, comprising:

[0017] 1) Sodium nickel iron manganese oxide, conductive agent SP, CNT, and binder PVDF are mixed in proportion to obtain positive electrode slurry, and the positive electrode slurry is coated on the surface of the foil, dried, rolled, and cut to obtain a positive electrode sheet.

[0018] 2) Hard carbon, conductive agent SP, CNT, CMC, and binder SBR are mixed in proportion to obtain negative electrode slurry, and the negative electrode slurry is coated on the surface of the foil, and the negative electrode sheet is obtained after drying, rolling, and slitting.

[0019] 3) Winding the positive electrode sheet, the negative electrode sheet and the separator to obtain a winding core, and then vacuum baking, liquid injection, aging, chemical formation and aging are performed.

[0020] Preferably, step 3) comprises: winding the positive electrode sheet, the negative electrode sheet and the diaphragm to obtain a winding core, flattening the positive and negative electrodes of the winding core and welding the positive and negative electrode collectors, placing the winding core into a steel shell, using a bottom laser to weld the negative electrode collector, and rolling grooves at the shell mouth; placing the semi-finished battery after rolling grooves into a vacuum oven, baking, cooling and taking out the battery cell, injecting the electrolyte into the battery, laser welding the positive electrode collector and the cap, and mechanically sealing the cap and the steel shell; placing the sealed battery into an aging room, aging for 24 to 48 hours, and then performing formation and aging.

[0021] The beneficial effects of the present invention are at least that: the ultra-high rate large cylindrical sodium ion battery of the present invention can achieve 8C continuous charging at room temperature, 10C continuous discharge, 50C pulse discharge, and 30C pulse discharge at -20°C. At the same time, the steel shell large cylindrical battery has better structural stability and safety reliability. Most of the use scenarios in application fields such as electric vehicles, electric ships, electric tools, drones, start-stop power supplies, etc. will face high temperature and high humidity, high frequency vibration, and wide temperature harsh conditions. The ultra-high rate large cylindrical sodium ion of the present invention can meet the above application fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1A schematic structural diagram of an ultra-high rate sodium ion battery provided in an embodiment of the present invention.

[0024] Figure 2 This is the rate discharge curve of the ultra-high rate sodium ion battery provided in Example 3 of the present invention.

[0025] Figure 3 This is the rate charging curve of the ultra-high rate sodium ion battery provided in Example 3 of the present invention.

[0026] Figure 4 This is a 30C pulse discharge diagram of the ultra-high rate sodium ion battery provided in Example 3 of the present invention.

[0027] Figure 5 This is a 50C pulse discharge diagram of the ultra-high rate sodium ion battery provided in Example 3 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products or can be prepared by known methods. If no specific techniques or conditions are specified in the examples, they are all conventional methods or carried out according to the techniques or conditions described in the literature in the field, or according to the product instructions. The reagents and instruments used, etc., for which the manufacturers are not specified, are all conventional products that can be purchased through regular channels. In the embodiments of the present invention, the main material of the positive electrode is sodium nickel iron manganese oxide; the main material of the negative electrode is hard carbon, and the main materials of the positive and negative electrodes are selected from 2-8μm small particle size materials; the ceramic diaphragm is a PE ceramic diaphragm, and the electrolyte is a commonly used sodium salt organic solvent system (sodium hexafluorophosphate, ethyl methyl carbonate).

[0030] The present invention will be further described below with reference to the embodiments.

[0031] Example 1 This embodiment provides an ultra-high rate sodium ion battery ( Figure 1 ), the preparation method of the ultra-high rate sodium ion battery is as follows.

[0032] Preparation of positive electrode sheet: prepare slurry according to 95.9%wt of sodium nickel iron manganese oxide, 1.8%wt of conductive agent SP, 0.8%wt of multi-walled carbon nanotubes MWCNT, and 1.5%wt of PVDF. The coating density of the positive electrode sheet is 260g / m², the compaction density is 3.2g / cm³, and the foil material is 13μm carbon-coated aluminum foil (the substrate thickness is 12μm, and the carbon coating layer thickness is 1μm).

[0033] Preparation of negative electrode sheet: prepare slurry according to 94.5%wt of hard carbon, 1.2%wt of conductive agent SP, 0.3%wt of single-walled carbon nanotube SWCNT, 1.5%wt of CMC and 2.5%wt of binder SBR. Apply the negative electrode slurry on the surface of carbon-coated aluminum foil with a coating surface density of 120g / m² and a compaction density of 1.0g / cm³. After drying, rolling and slitting, the negative electrode sheet is obtained.

[0034] Core preparation: The positive electrode sheet, negative electrode sheet and ceramic diaphragm (porosity 46%) are wound to make the core. After the positive and negative electrodes of the core are flattened, the positive and negative current collectors are welded. The core is placed in a steel shell, the negative current collector is welded using a bottom laser, and grooves are rolled at the shell mouth.

[0035] Vacuum baking and liquid injection: put the semi-finished battery after grooving into a vacuum oven and bake it at 95℃ for 10 hours. After cooling down, take out the battery cell and inject the sodium ion organic solvent system electrolyte into the battery. Laser weld the positive electrode collector and the cap, and mechanically seal the cap and the steel shell.

[0036] Aging, formation, and aging: Place the sealed battery in an aging room for 24 hours, then perform formation and aging to complete the battery preparation.

[0037] Example 2 The difference from Example 1 is: Preparation of positive electrode sheet: slurry is prepared according to 96.2%wt of sodium nickel iron manganese oxide, 1.8%wt of conductive agent SP, 0.5%wt of single-walled carbon nanotube SWCNT, and 1.5%wt of PVDF. The coating surface density of the positive electrode sheet is 260g / m², and the foil material is 21μm carbon-coated aluminum foil (the substrate thickness is 20μm, and the carbon coating layer thickness is 1μm).

[0038] Example 3 The difference from Example 1 is: Preparation of positive electrode sheet: slurry is prepared according to 95.9%wt of sodium nickel iron manganese oxide, 1.8%wt of conductive agent SP, 0.8%wt of single-walled carbon nanotube SWCNT, and 1.5%wt of PVDF. The coating surface density of the positive electrode sheet is 220g / m², and the foil material is 21μm carbon-coated aluminum foil (the thickness of the substrate is 20μm, and the thickness of the carbon coating layer is 1μm).

[0039] Example 4 The difference from Example 1 is: Preparation of positive electrode sheet: slurry is prepared according to 95.9%wt of sodium nickel iron manganese oxide, 1.8%wt of conductive agent SP, 0.8%wt of multi-walled carbon nanotubes MWCNT, and 1.5%wt of PVDF. The coating surface density of the positive electrode sheet is 220g / m², and the foil material is 13μm carbon-coated aluminum foil (the thickness of the substrate is 12μm, and the thickness of the carbon coating layer is 1μm).

[0040] The performance test of the battery of each example was carried out. The test method of the discharge capacity ratio at 25°C was as follows: 1) Standing for 1 min; 2) 1C constant current discharge to 1.5V; 3) Standing for 30 min; 4) 1C constant current constant voltage charge to 3.95V, cut-off current 0.05C; 5) Standing for 30 min; 6) 1C constant current discharge to 1.5V; 7) Standing for 30 min; 8) 1C constant current constant voltage charge to 3.95V, cut-off current 0.05C; 9) Standing for 30 min; 10) 4C constant current discharge to 1.5V; 11) Standing for 60 min; 12) 1C constant current constant voltage charge to 3.95V, cut-off current 0.05C Current 0.05C; 13) Stand for 30min; 14) 6C constant current discharge to 1.5V; 15) Stand for 90min; 16) 1C constant current constant voltage charge to 3.95V, cut-off current 0.05C; 17) Stand for 30min; 18) 8C constant current discharge to 1.5V; 19) Stand for 120min; 20) 1C constant current constant voltage charge to 3.95V, cut-off current 0.05C; 21) Stand for 30min; 22) 10C constant current discharge to 1.5V; Divide the discharge capacity of step 7, 11, 15, and 19 by the discharge capacity of step 3, and calculate the discharge capacity ratio at different C rates. The test results are shown in the following table (" / " means that discharge is not possible at this C rate).

[0041] The test results of the battery of Example 3 of the present invention at different C rates of continuous charging, 50C pulse discharge, and 30C pulse discharge at -20°C are as follows: Figure 3-Figure 5 As shown, it can be seen that the ultra-high rate large cylindrical sodium ion battery of the present invention realizes continuous charge and discharge and pulse discharge at different C rates and temperatures, and has excellent comprehensive performance.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sodium ion battery, characterized in that: The sodium ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator; the positive electrode sheet includes sodium nickel iron manganese oxide, a conductive agent SP, CNT and a binder PVDF; the negative electrode sheet includes hard carbon, a conductive agent SP, CNT, CMC and a binder SBR; the mass ratio of the sodium nickel iron manganese oxide, the conductive agent SP, CNT and the binder PVDF in the positive electrode sheet is (95.5-96.5): (1.2-1.9): (0.4-1.2): (1.2-1.6).

2. The sodium ion battery according to claim 1, characterized in that The foil material of the positive electrode sheet and / or the negative electrode sheet comprises a substrate and a carbon coating layer covering the surface of the substrate, the substrate thickness is 12-25 μm, and the carbon coating layer thickness is 1-3 μm; the foil material is carbon-coated aluminum foil.

3. The sodium ion battery according to claim 1, characterized in that: In the positive electrode sheet, the mass ratio of the sodium nickel iron manganese oxide, the conductive agent SP, the CNT and the binder PVDF is (95.9-96.2): ​​(1.5-1.8): (0.5-0.8): (1.3-1.5).

4. The sodium ion battery according to any one of claims 1 to 3, characterized in that: In the negative electrode sheet, the mass ratio of the hard carbon, the conductive agent SP, CNT, CMC and the binder SBR is (94-95): (1-1.5): (0.5-1): (1.2-1.8): (2.3-2.8).

5. The sodium ion battery according to any one of claims 1 to 3, characterized in that: In the positive electrode sheet and / or the negative electrode sheet, the CNT is a multi-walled carbon nanotube MWCNT and / or a single-walled carbon nanotube SWCNT.

6. The sodium ion battery according to any one of claims 1 to 3, characterized in that: The particle size of the sodium nickel iron manganese oxide in the positive electrode sheet and / or the hard carbon in the negative electrode sheet is 2-8 μm.

7. The sodium ion battery according to any one of claims 1 to 3, characterized in that: The diaphragm is a ceramic diaphragm coated with alumina or boehmite, and the porosity of the diaphragm is 40-50%.

8. The sodium ion battery according to any one of claims 1 to 3, characterized in that: The electrolyte is a sodium salt organic solvent system.

9. The sodium ion battery according to any one of claims 1 to 3, characterized in that: The sodium ion battery is a large cylindrical sodium ion battery, and the positive terminal and the negative terminal adopt a full-ear structure.

10. The method for preparing a sodium ion battery according to any one of claims 1 to 9, characterized in that: include: 1) Sodium nickel iron manganese oxide, conductive agent SP, CNT, and binder PVDF are mixed in proportion to obtain a positive electrode slurry, and the positive electrode slurry is coated on the surface of the foil, dried, rolled, and cut to obtain a positive electrode sheet; 2) Mixing hard carbon, conductive agent SP, CNT, CMC, and binder SBR in proportion to obtain negative electrode slurry, coating the negative electrode slurry on the surface of the foil, drying, rolling, and slitting to obtain a negative electrode sheet; 3) Winding the positive electrode sheet, the negative electrode sheet and the separator to obtain a winding core, and then vacuum baking, liquid injection, aging, chemical formation and aging are performed.

Citation Information

Patent Citations

  • Carbon nanotube conductive slurry and method for preparing carbon nanotube conductive slurry

    CN103426498A

  • Method for using carbon nano conductive agent in lithium ion battery aqueous slurry

    CN103840164A

  • Low-temperature-resistant sodium ion battery

    CN113851632A

  • Sodium-ion battery positive electrode slurry, sodium-ion battery and preparation method of sodium-ion battery

    CN116314803A

  • Preparation method of high-energy-density sodium ion cylindrical battery

    CN117913258A

Cited By

  • Sodium-ion battery capacitor and preparation method thereof

    CN120637119A